Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features - Miko, Ladislav; Ermilov, Sergey G. (Zootaxa, 2017)
A new oribatid mite genus, Tamdamaeus gen. nov., with its type species, Tamdamaeus staryi sp. nov., belonging to the family Damaeidae, is proposed and described from leaf litter and soil from Tam Dao National Park (Northern Vietnam). It is close to the genus Damaeus C.L. Koch, 1835, but differs from the latter by the absence of spinae adnatae on the notogaster and by specific leg setation with 6 setae on femora II and IV. The position of the new taxa within related genera and species is discussed.